The search-ification of everyday life and the mundane-ification of search. Issue 2 (13th March 2017) - Sundin, Olof; Haider, Jutta; Andersson, Cecilia; Carlsson, Hanna; Kjellberg, Sara
Abstract : Purpose: The purpose of this paper is to understand how meaning is assigned to online searching by viewing it as a mundane, yet often invisible, activity of everyday life and an integrated part of various social practices. Design/methodology/approach: Searching is investigated with a sociomaterial approach with a starting point in information searching as entangled across practices and material arrangements and as a mundane part of everyday life. In total, 21 focus groups with 127 participants have been carried out. The study focusses particularly on peoples' experiences and meaning-making and on how these experiences and the making of meaning could be understood in the light of algorithmic shaping. Findings: An often-invisible activity such as searching is made visible with the help of focus group discussions. An understanding of the relationship between searching and everyday life through two interrelated narratives is proposed: a search-ification of everyday life and a mundane-ification of search. Originality/value: The study broadens the often narrow focus on searching in order to open up for a research-based discussion in information science on the role of online searching in society and everyday life.